Spiking kinematics in volleyball players with shoulder pain - Shih, Y.-F.; Wang, Y.-C. (Journal of Athletic Training, 2019)
Context Spiking is one of the most frequently used scoring techniques in volleyball games, and around 80% of shoulder pain in volleyball players is linked with the spiking movement.